RECURRENT ORAL AND OROPHARYNGEAL CANCER: CLINICAL PICTURE, DIAGNOSIS, AND TREATMENT - I. A. Zaderenko; S. B. Aliyeva; A. Yu. Drobyshev; R. I. Azizyan (Klinicist)
Malignant oral tumors account for 6 % in the total cancer incidence. The rate of recurrent tumors ranges from 25 to 50 %. About 80 % of patients with failed treatment are to undergo radiation, chemoradiation, or drug therapy. After retreatment, severe complications occur in more than half of the patients even to death (2 %). Some progress has been made in the treatment of recurrent tumors due to the current possibilities of surgical treatment. Surgical reintervention can be made and satisfactory treatment results obtained in a number of patients even if they develop recurrent tumor after a previous saving operation.